Celastrol: A Promising Agent Fighting against Cardiovascular Diseases - Zhexi Li; Jingyi Zhang; Xulei Duan; Guoan Zhao; Min Zhang (Antioxidants, 2022)
Cardiovascular diseases (CVD) are leading causes of morbidity and mortality worldwide; therefore, seeking effective therapeutics to reduce the global burden of CVD has become increasingly urgent. Celastrol, a bioactive compound isolated from the roots of the plant Tripterygium wilfordii (TW), has been attracting increasing research attention in recent years, as it exerts cardiovascular treatment benefits targeting both CVD and their associated risk factors. Substantial evidence has revealed a protective role of celastrol against a broad spectrum of CVD including obesity, diabetes, atherosclerosis, cerebrovascular injury, calcific aortic valve disease and heart failure through complicated and interlinked mechanisms such as direct protection against cardiomyocyte hypertrophy and death, and indirect action on oxidation and inflammation. This review will mainly summarize the beneficial effects of celastrol against CVD, largely based on in vitro and in vivo preclinical studies, and the potential underlying mechanisms. We will also briefly discuss celastrol’s pharmacokinetic limitations, which hamper its further clinical applications, and prospective future directions.